Procedural incompliance marriage: A case study in Terengganu - Asiah, Bidin; Akmal, Mohamad; Kamaliah, Salleh; Noraida, Harun; Noor ‘Ashikin, Hamid (2016)
Marriage is a union of two individuals, a man and a woman to form a family. Islam has set the laws and regulations in marriage. In addition, the Administration of Islamic Family Law Enactment in each state also setforth specific rules and procedures so that the purpose and objectives of marriage can be achieved, and also the marriage simultaneously be rewarded with the blesses of Allah. The Islamic Religious Affairs Department is the enforcement body which looks into the implementation of the rules and procedures. Even so, the public in Malaysia often exposed to cases of breach of procedures and rules established by such enactment. This study discusses the marriage procedure under the Administration of Islamic Family Law (Terengganu) Enactment 1985. In addition, this article also highlights cases that did not comply with the procedures, which have implications in term of confirmation application of marriage in Syariah courts in Terengganu. The study was conducted based on the analysis of documents, particularly the Administration of Islamic Family Law (Terengganu) Enactment 1985, and the data obtained from Terengganu Syariah courts, as well as interviews with the officials at the Kuala Terengganu Syariah Court.